0178 The Cycle of Daily Stress and Sleep: Sleep Measurement Matters. (27th May 2020) - Slavish, D C; Asbee, J; Veeramachaneni, K; Messman, B; Scott, B; Walker, J; Sin, N L; Taylor, D J; Dietch, J
Abstract: Introduction: Disturbed sleep can be both a cause and a consequence of increased stress. Yet intensive longitudinal studies have demonstrated that sleep assessed via sleep diaries and actigraphy is inconsistently associated with daily stress. We expanded this research by examining daily associations between sleep and stress using a three-fold approach to assess sleep: sleep diaries, actigraphy, and ambulatory single-channel electroencephalography [EEG]. Methods: Participants were 80 adults ( M age = 32.65 years, 63% female) who completed 7 days of sleep and perceived stress assessments in a naturalistic setting (resulting in 560 possible measurement occasions). Multilevel models were used to examine bidirectional associations between daily stressor occurrence (0 = stressor did not occur, 1 = stressor occurred) and stressor severity (0 = not at all severe to 3 = very severe) and sleep parameters assessed via diary, actigraphy, and EEG (e.g. total sleep time [TST], sleep efficiency [SE], and sleep onset latency [SOL], wake after sleep onset [WASO]). Results: Participants reported at least one stressor on 37% of days. Compared to days without a stressor experienced, days with a stressor were associated with a 14.4-minute reduction in actigraphy-determined TST the subsequent night (β = -0.24, p = 0.030). Nights with greater sleep-diary determined WASO were associated with greater next-day stressor severity (β = 0.01, p = .026). No EEG-determined sleep parameters were associated with next-day stressor occurrence or severity, or vice versa. Conclusion: Daily stress and sleep disturbances occurred in a bidirectional fashion, though specific results varied by sleep measurement technique and sleep parameter. Together, our results highlight that type of sleep measurement matters for examining associations with daily stress. We urge future researchers to treat sleep diaries, actigraphy, and EEG as complementary — not redundant — sleep measurement approaches. Support: Funding for this study included NIH/NIAID R01AI128359-01; DoD-VA 1I01CU000144-01; the Foundation for Rehabilitation Psychology; and General Sleep Corporation.